Proposta de plano de manejo para o Geossítio Gruta do Índio, Geoparque Quarta Colônia Aspirante Unesco - Vestena, Michele Hennig (2023)
In Brazil, most legal means of protection offer greater attention to biodiversity, often leaving the abiotic portion with less priority. In this sense, Geoconservation emerges, which is a set of actions and strategies that aim to prevent the abiotic portion of nature from being destroyed. One of the strategies to promote geoconservation in a global level, are the Geoparks, and in the central region of the state of Rio Grande do Sul, the Geopark Quarta Colônia strategy stands out. The initiative aspires to be part of the Global Geoparks Network, motivated by several potentialities, the main one being the fossils found in rocky outcrops dating from the Triassic. Among the assets of geomorphological value are the caves in siliciclastic rocks, like the Gruta do Índio, in Agudo, which suffers from depredations, given the lack of visitor control and a visitation strategy. In this sense, the present work sought to carry out a detailed interdisciplinary inventory of the Gruta do Índio Geosite area, as a subsidy to propose visitation strategies that avoid the heritage degradation and which may strengthen geotourism in the Quarta Colônia Aspiring Geopark. In a first analysis, it was found that few natural cavities in Rio Grande do Sul are protected, which demonstrates the urgency of expanding discussions regarding the protection of these geodiversity features. In relation to the geosite, it was verified that it has an interdisciplinary character, being classified as of anthropological, ecological, touristic, didactic and scientific interest, the latter being little explored in relation to the existing potential. A delimitation for the Geosite was proposed, with 3 differentiated zones: it can be classified as a conservation zone, an area of use of natural resources, and a geo-heritage protection area, which prioritizes the protection of the cave. Regarding the proposed management measures, these can be summarized in two main strategies: the implementation of environmental education actions, and investment in infrastructure and interpretive material. One identified possibility to leverage tourism in the geosite was to insert the place in regional "tours", with the integration of other nearby attractions. Proposed interpretive materials include content for an interpretive panel, configuring itself as the most appropriate interpretation strategy for the location. Finally, it is expected that this work will serve as a basis for conservation measures to be applied in the area of the Geosite Gruta do Índio, and that it will serve as a source for studies of other natural cavities in siliciclastic rocks existing in the territory of the Geopark Quarta Colônia aspiring UNESCO, allowing the use of these environments of such great heritage value in the most sustainable way possible.